Carmen Castillo et Catalina Villar : l’entre-deux du lieu d’énonciation du « latino-américain » - Amanda Rueda (Caravelle)
There are many films directed by Latin-American film-producers living in Europe who go back home to shoot. Therefore the place of cinematographic enunciation defines itself by taking into consideration this aspect of inter-land : the starting-point territory and the welcoming one. A purely geographical dislocation at the beginning gives, of course, particular aspects to their way of representing the world and changes the relation with their country and their continent. What are the distinctive features of the documentaries of this inter-land of the « Latin-American » ? The article tries to answer this question through the reading of Rue Santa Fe (Santa Fe Street) and Bienvenus en Colombie (Welcome to Colombia), shot by the Chilean Carmen Castillo and the Columbian Catalina Villar, two film-producers working in France.